2009
DOI: 10.1074/jbc.m109.016600
|View full text |Cite
|
Sign up to set email alerts
|

Human Heart Mitochondrial DNA Is Organized in Complex Catenated Networks Containing Abundant Four-way Junctions and Replication Forks

Abstract: Analysis of human heart mitochondrial DNA (mtDNA) by electron microscopy and agarose gel electrophoresis revealed a complete absence of the θ-type replication intermediates seen abundantly in mtDNA from all other tissues. Instead only Y- and X-junctional forms were detected after restriction digestion. Uncut heart mtDNA was organized in tangled complexes of up to 20 or more genome equivalents, which could be resolved to genomic monomers, dimers, and linear fragments by treatment with the decatenating enzyme to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
149
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(160 citation statements)
references
References 71 publications
8
149
1
2
Order By: Relevance
“…Overexpression of Twinkle was shown to increase the presence of Holliday junction type structures in heart mtDNA of transgenic mice (45). These findings coupled with observations that the major strand exchange recombination protein Rad51 and the related HR proteins Rad51C and Xrcc3 are found in human mitochondria (46) suggest that HR repair of mitochondrial double strand breaks is likely to be important for maintaining genome stability in the organelle.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Overexpression of Twinkle was shown to increase the presence of Holliday junction type structures in heart mtDNA of transgenic mice (45). These findings coupled with observations that the major strand exchange recombination protein Rad51 and the related HR proteins Rad51C and Xrcc3 are found in human mitochondria (46) suggest that HR repair of mitochondrial double strand breaks is likely to be important for maintaining genome stability in the organelle.…”
Section: Discussionsupporting
confidence: 58%
“…Electron microscopy and agarose gel analyses have provided evidence that human heart mtDNA contains multimeric junctional DNA complexes, including four-way and three-way junctions typically associated with replication forks or intermediates of HR repair (45). Overexpression of Twinkle was shown to increase the presence of Holliday junction type structures in heart mtDNA of transgenic mice (45).…”
Section: Discussionmentioning
confidence: 99%
“…60 and 61). Notably, recent electron microscopic studies have revealed the presence of abundant four-way and three-way junctions suggestive of recombination intermediates in the oxyradical-rich human adult heart and brain mitochondria (62)(63)(64). A low level of recombination, which is probably limited between intranucleoidal mtDNA molecules (65), may be in place in animal mitochondria from specific tissues as an effective mechanism for mutational clearance while minimizing the invasion by selfish DNAs (66).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a laboratory strain of mice there was no evidence of intermolecular mtDNA recombination in the germ-line over the course of 50 generations [42]. An ability to resolve recombination junctions might be required at the end of the replication cycle as found for bacteria [43], and be necessary to regulate the networks of mtDNA molecules that form in adult human heart [44]. It is unlikely that mitochondria can create such DNA structures and yet be unable to resolve or otherwise process them.…”
Section: The Machinery Of Mtdna Selectionmentioning
confidence: 99%